Muslim-Christian Relationships In Indonesian Reform Era Within The Framework Of Democracy: Case Study Of Bandung, Bekasi And Bogor (1998-2015) - Damayanti, Angel (2018)
A relatively peaceful relationship between Muslims and Christians in Indonesia has been dotted by religious intolerance and worship restrictions in the form of churches destruction, bannings and closures, which mostly happened in Bandung, Bekasi and Bogor. This research utilizes qualitative methodology including the case studies, historical studies and triangulation method. By employing theories of democracy and democratization, decentralization, human rights and the role of international organization in promoting human rights, this study finds that Muslim-Christian relationship in Indonesia have been spoiled by reciprocal threat perception since their first encounter in terms of the suspicion of Christianization vis a vis the suspicion of the establishment of an Islamic state. This is in addition to the rise of radical Islamic groups, the obscurity on delegation of authority in decentralization system and the contradicting regulations, the ignorance of government to take firm measures, and the poor management on the issue of denominations within Christian adherents